Training on the Use of Appropriate Technology to Increase Agricultural Production in Villages in Indonesia - Siswanto, Agus; Haji, Wachyu Hari; Suryadi, Dikky; Hady, Sultan; Setiawan, Zunan (Unram Journal of Community Service, 2024)
This Community Service activity aims to improve the knowledge and skills of farmers in Indonesia's villages by using appropriate technology through online training. In this series of activities, villages with adequate internet infrastructure and a low rate of technology adoption are identified. The training was conducted online using the Zoom application and attended by farmers from various regions. The results of the pre-test show that the majority of farmers have limited knowledge about agricultural technology. After participating in the training, the final assessment (post-test) showed a significant improvement in farmers' knowledge and skills, with an average increase in knowledge scores of 60% and skills of 55%. High participation and positive feedback from participants indicate the effectiveness of online training as a method to increase farmers' capacity. However, challenges such as limited access to equipment and cost remain obstacles to implementing appropriate technology in the field. In conclusion, online training has improved farmers' knowledge and skills. Still, additional support is needed to ensure the sustainability of the application of technology in the field. These findings make an important contribution to the development of farmer capacity-building programs in Indonesia, especially in the context of the adoption of modern agricultural technology.